Effect of oxygen flow ratio on the performance of RF magnetron sputtered Sn-doped Ga2O3 films and ultraviolet photodetector. Issue 7 (1st April 2023) - Wang, Chen; Fan, Wei-Hang; Zhang, Yu-Chao; Kang, Pin-Chun; Wu, Wan-Yu; Wuu, Dong-Sing; Lien, Shui-Yang; Zhu, Wen-Zhang
Abstract: This work explored the properties of RF magnetron sputtered Sn-doped Ga2 O3 films grown on sapphire substrates at different oxygen flow ratios from 0.0 to 2.5%. The in situ optical emission spectroscopy was conducted to monitor the plasma radicals generated during the films' deposition. All the films deposited at room temperature show amorphous structures with some nanoparticles. The deposition rate decreased monotonically with increasing oxygen flow ratio. The proposed conductive mechanism of the films can be mainly attributed to the changes in the ratio of substitutional Sn (Sn 4+ valance state) atoms replacing lattice Ga sites (Ga 3+ valance state) and the SnO2 phase in the films. Metal–semiconductor–metal solar-blind photodetectors were developed and analyzed to illustrate the effect of oxygen flow ratio. A high performance photodetector with a low dark current of 1.14 pA, high on/off ratio of 812 and short rise/decay time of 0.05 s/0.12 s was realized at an optimization growth condition. The elaboration of the conductive mechanism and effect of oxygen flow ratio on the performance of Sn-doped Ga2 O3 films and their photodetectors is crucial for the preparation of high-quality Sn-doped Ga2 O3 films and its application in optoelectronic devices.